Persepsi Mahasiswa Terhadap Konten Beautyinfluencer di Tiktok (Studi Kasus Masker Clay Stick Mugwort Skintific) - Salsabila, Fahira; Hidayah, Nurul; Ambarwati, Neneng Siti Silfi (Innovative: Journal Of Social Science Research, 2025)
This study examines the perceptions of female students in the Beauty and Cosmetic Care Study Program regarding beauty influencer content on the TikTok platform, specifically regarding the Skintific Mugwort Clay Stick Mask. Against the backdrop of TikTok's increasing popularity as a digital marketing medium and the significant role of beauty influencers in shaping consumer opinion, this study aims to understand how student perceptions influence their intention to purchase these beauty products. A descriptive qualitative method was used with six purposively selected female students, involving in-depth interviews, content observation, and data documentation. The results indicate that students view beauty influencers as credible and inspiring sources of information, but remain selective, conducting additional verification before making a purchase. Content quality, social interaction, and influencer reputation also influence purchasing decisions. This study confirms that despite the strong influence of influencers, students' purchasing decisions are influenced by various critical considerations. Therefore, the role of beauty influencers is not absolute dominance, but rather part of a complex and active information ecosystem. These findings provide important insights for digital marketing strategies that seek to maximize influencer influence while maintaining the credibility and trust of young consumers.